pengembangan layanan informasi karir melalui media wayang untuk pengenalan profesi anak sd - Ali Murtadlo (JPGI (Jurnal Penelitian Guru Indonesia), 2022)
The media in providing guidance and counseling services can be used as a tool for transferring career information service materials in elementary schools which aim to help students prepare for their future choices. The media used is a wayang profesi. The development of this wayang profesi uses the Research and Development (R&D) model. Using the research and development model from Borg and Gall. Assessment of development products carried out by 2 experts. Consisting of BK material experts and PGSD media experts. and carried out by 1 product user, namely the social studies teacher at MI Al Latifiyah. In the product assessment, quantitative and qualitative data were obtained, and were processed using descriptive analysis techniques. Based on the assessment of the two expert tests, it can be concluded that the development of career information services through wayang media fulfills the criteria. for the relevance aspect of the material (4,8) the material presented is very relevant, while the accuracy of the material (4,6) the material presented is very accurate, and for the readability and communicative aspects of the material (4) it is very legible and communicative, as well as the feasibility of the media (4, 1) which means that the media is very feasible to be developed and used as an alternative media. The test results of product users show the attainment value (4.1) which means very appropriate. From these results it can be concluded that wayang profesi are suitable as a medium by counselors in providing career information services for elementary school students. Suggestions for further research are to be able to carry out trials to a wider field test.